STUDI ANALISIS PENANGANAN LONGSOR PADA SLOPE TIMBUNAN YANG TEGAK (STUDI KASUS LONGSORAN DI JALAN TOL RUAS SEMARANG – BAWEN KM 426+600) - Ade Gunawan (Universitas Darul Ulum Islamic Centre Sudirman GUPPI, 2020)
Heavy rains that flushed most of the Semarang area have resulted in the slope on the edge of the Semarang - Bawen STA.426 + 600 toll road experiencing landslides and eroding part of the shoulder of the road. A slope stability analysis is needed to determine the slope safety factor at the research location which can model it according to the original conditions in the field so that there is an approach condition in the analysis results and makes it easier to model its handling, one of which is by using manual formulas.In this analysis, the input data for soil parameters were used, including: cohesion, c; angle of shear in soil, ðœ‘; slope angle, ð›¼; and soil volume weight, ð›¾. From the results of the analysis of slope stability with cantilever wall reinforcement, it is considered safe because the foundation soil stress that occurs is smaller than the allowable stress of the soil, namely (664,556 <1496,219) for normal conditions and (464,951 <1496,219) for earthquake conditions. SF to shear under normal conditions is greater than the required SF (3,738> 1,5). SF to shear earthquake conditions is greater than the required SF (3.036> 1.2). The SF against rolling under normal conditions is greater than the required SF (2,068> 2). SF against rolling earthquake conditions greater than the required SF (1.912> 1.5).Keywords: Semarang - bawen toll road, landslides, slope analysis